Level of glycemic control among US type 2 diabetes mellitus patients on dual therapy of metformin and sodium–glucose cotransporter 2 inhibitor: a retrospective database study. (2nd October 2020) - Lautsch, Dominik; Iglay, Kristy; Yang, Lingfeng; Bansal, Neha; Markan, Riddhi; Kathe, Niranjan; Rajpathak, Swapnil
Abstract: Objective: To assess the level of glycemic control among type 2 diabetes patients on sodium-glucose cotransporter 2 inhibitor (SGLT2i) and metformin dual therapy. Methods: Observational, retrospective database study in adult type 2 diabetes mellitus patients from the IQVIA Electronic Medical Record (EMR) database was conducted. The observation period was June 2015 to June 2018. Patient's earliest encounter in the observation period while on SGLT2i and metformin dual therapy served as the index date. Patients were required to have at least one HbA1c measure in the 12 months prior to the index date and be on SGLT2i and metformin dual therapy and no other antihyperglycemic treatment as of the HbA1c measurement date or any time during the 90 days prior. The associations between sociodemographic factors and clinical burden on achievement of HbA1c <8% were assessed using multivariable logistic regression with backward stepwise selection. Results: Of 3491 patients, 2176 (62.3%) achieved HbA1c <8%, with a median distance to goal of 1.1% (IQR 0.5–2.3%) for those not at glycemic target. Mean age was 56.5 years and 52.6% were male. At baseline, 28.3% of patients had established cardiovascular disease/chronic kidney disease, and of those 63.8% had HbA1c <8%. African American patients had lower odds of attaining HbA1c <8% when compared with white patients [OR 0.69], while older patients had marginally higher odds [OR 1.01]. Conclusion: Approximately 3 out of 5 patients on metformin and SGLT2i dual therapy achieved HbA1c <8%, with African Americans having a lower likelihood of achieving this glycemic goal.